2005
DOI: 10.1177/1077801204271662
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Intimacy

Abstract: This article describes the findings of research into judicial decision making in Ontario courts in cases of intimate violence against women. Judges are condemning the violence, issuing relatively harsh sentences, and arguing that the intimate context of the violence is an aggravating factor. The analysis also reveals that judges often rely on stereotypes and traditional notions of marriage, family, and femininity. As records of decisions, the documents suggest a high level of understanding that wife abuse is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The Ottawa City Police Service, prosecutors, and court-based victim services liaise with each other to obtain ODARA scores for male perpetrators and communicate with women's shelters and related agencies with a shared language for discussing risk (Ontario Ministry of the Attorney General, 2006). Although we know of no empirical evaluation of this particular model, the Attorney General of Ontario recognized PAST with an award of excellence in 2006; furthermore, a recent analysis of judicial decision making in Ontario courts concluded that, more often than not, judges strongly condemned partner violence against women, issued custodial sentences, and frequently considered the intimate context of the violence as an aggravating factor (Crocker, 2005).…”
Section: Coordinated Criminal Justice and Community Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ottawa City Police Service, prosecutors, and court-based victim services liaise with each other to obtain ODARA scores for male perpetrators and communicate with women's shelters and related agencies with a shared language for discussing risk (Ontario Ministry of the Attorney General, 2006). Although we know of no empirical evaluation of this particular model, the Attorney General of Ontario recognized PAST with an award of excellence in 2006; furthermore, a recent analysis of judicial decision making in Ontario courts concluded that, more often than not, judges strongly condemned partner violence against women, issued custodial sentences, and frequently considered the intimate context of the violence as an aggravating factor (Crocker, 2005).…”
Section: Coordinated Criminal Justice and Community Responsesmentioning
confidence: 99%
“…This was partly because reformers depended on positions of influence they had through other, less radical movements (i.e., suffrage and temperance), and it was not until the 1960s that the new women's movement recognized partner violence against women as a problem with its own priority. The need to present battered women as "weak victims" in order to gain legitimacy continued in family courts in the late 20th century (Hilton, 1991; see also Bograd, 2005;Crocker, 2005). Critical analysis of criminal justice responses to partner violence also abandoned women who used violence, substance abusers, and other "less virtuous" victims and has only recently focused on responses to women of color and women in same-sex relationships (e.g., see Sokoloff & Pratt, 2005).…”
Section: Criminal Justice Response To Women Perpetrators and Marginal...mentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized a mixed-method model for content analysis of judicial decisions (Crocker 2005). We integrated quantitative and qualitative methods of content analysis to gain a thick understanding of the sociolegal construction of disability and sexuality in Israeli tort law.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This research focused on various criminal justice officials including police officers (Eitle, 2005;Felson, Ackerman, & Gallagher, 2005;Van Hasselt & Malcolm, 2005), judges (Crocker, 2005), prosecutors (Hartman & Belknap, 2003), and probation officers (Hofford, 1991). Three themes arose in these studies.…”
Section: Review Of Literaturementioning
confidence: 99%